Sosialisasi Pola Makan Prediabetes: Cara Tepat Cegah Diabetes: Sosialisasi Pola Makan Prediabetes: Cara Tepat Cegah Diabetes - Dewi Perwito Sari; Prisma Trida Hardani; Nadya Ambarwati; Amanda Safitri Sinulingga; Asri Wido Mukti; Eka Fitria (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Diabetes is a metabolic disorder disease characterized by blood sugar levels that exceed normal limits. The International Diabetes Federation shows that Indonesia is in the 5th position of the country with the most diabetes sufferers. The results of the 2018 Basic Health Research (RISKESDAS) show an increase in the number of people with diabetes. Before someone is diagnosed with diabetes, that person may have a condition called prediabetes. Diabetes which is a non-communicable disease can be prevented by lifestyle changes. The prevalence of diabetes sufferers in East Java Province is 2.6% and occupies the 4th position with the highest number of sufferers in Indonesia. Data from the Central Statistics Agency (BPS) shows that the population in the city of Surabaya in 2022 will reach 2.9 million people, the size of the population also affects the possibility of the number of diabetics. Therefore, education is needed about prediabetes and efforts to prevent and control diabetes through a healthy lifestyle. The Community Partnership Program (PKM) is implemented to provide solutions to health problems, especially in educating partners in changing lifestyles to become healthier, in order to prevent the development of pre-diabetes.